Mammalian yolk sac - an alternative source of stem cells - Priscilla Avelino Ferreira Pinto; Vitória Mattos Pereira; Lina Castelo Branco Motta; Matheus Ferreira de Almeida; Tiago Gonçalves dos Santos; Vanessa Cristina Oliveira; Luciana Cristina Machado; Carlos Eduardo Ambrósio (Brazilian Journal of Veterinary Medicine, 2021)
Fetal tissue-derived stem cells have been the subject of several studies. Among them, the yolk sac (YS) nourishes the embryo, synthesizes proteins and vitamins, and is the first hematopoietic site of the embryo. Stem cells derived from the YS can benefit several animal species as therapies aimed at tissue regeneration and immunological diseases. This review aims to describe the development, function, and possible dysfunctions of YS in different species, and consolidate the findings presented in the literature on the isolation, culture, and application of YS-derived stem cells from different mammals in regenerative medicine. Hematopoietic and mesenchymal stem cells have been previously investigated in the YS of different mammals; however, the culture media and isolation protocols differ between species. To date, no studies have been conducted using stem cells derived from the YS for cell therapy. Nevertheless, several domestic mammals have shown cellular markers characteristic of mesenchymal stem cells derived from the YS.